The degree to which teachers in the first episode of basic education have access to competence of education from their point of view (field study in Banyas city) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This research aims to explore the degree to which teachers of the first episode of basic education have the competence of education from the point of view of the teachers themselves, and differences in their views on their possession of these competencies are defined according to the two variables (years of experience, scientific qualification). to achieve the research objectives, the descriptive analytical approach was used, designed A (52) item questionnaire spread over three axes, then applied to a sample of (115) teachers distributed to the schools of the first episode of basic education in Banias city, during the first semester of the 2020-2021 .The results of the search confirmed the following:- The degree to which teachers in the first episode of basic education have the three levels of education has come at a high rate.- There are statistically significant differences due to the variable number of years of experience in teachers' view of the degree to which they possess educational skills in favor of longer years of experience.- There are statistically significant differences due to the variable scientific qualification in the view of teachers as to the degree to which they possess educational qualifications for university leave holders.      Based on the results of the research, the researcher suggested the following: Enabling teachers to have optimal access to basic educational environments , and the necessity of holding more specialized training courses in the areas of educational competencies,